2008
DOI: 10.1021/jp808825c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nanocrystalline CeO2−ZrO2 Solid Solutions by a Citrate Complexation Route: A Thermochemical and Structural Study

Abstract: The synthesis of nanocrystalline solid solutions of general formula Ce x Zr1−x O2 (x = 0.1, 0.25, 0.5, 0.75, and 0.9) using a citrate complexation technique was followed with thermochemical methods, and the resulting powders were characterized using X-ray diffraction (XRD) and electron microscopy (scanning electron microscopy and high-resolution transmission electron microscopy (HRTEM)). Qualitative analysis of XRD data indicated that the samples exhibited either a cubic (Fm3m) or a tetragonal (P42/nmc) phase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 28 publications
0
37
0
Order By: Relevance
“…From the SAED patterns ( Fig. 2(D3 and E3)), the pseudocubic structure could be identified [19,36]. Notably, the (1 1 1) plane was predominate in all samples.…”
Section: Tem Analysismentioning
confidence: 86%
“…From the SAED patterns ( Fig. 2(D3 and E3)), the pseudocubic structure could be identified [19,36]. Notably, the (1 1 1) plane was predominate in all samples.…”
Section: Tem Analysismentioning
confidence: 86%
“…The product gas was chilled, passed through a trap to condense the residual water, and then analyzed on-line using an Agilent micro-gas chromatograph. [32] reported that nano-crystalline ceria-zirconia solid solution exhibited either cubic or tetragonal phase depending upon CeO 2 content. They applied Rietveld refinement method to know the phases present in the nano crystalline ceria-zirconia solid solution.…”
Section: Catalytic Reactionmentioning
confidence: 99%
“…These anodes were prepared as porous metal-ceramic composites, using optimized Ni charges and high surface Ce/Zr supports prepared at relative low temperatures, T ≤ 1,273 K. However, the crystal structure of low temperature prepared samples could differ considerably from that of high temperature phases prepared in this work, where Ce and Zr dilution is favored at high temperatures in intermediate compositions, improving the OSC behavior. The segregation of tetragonal Zr-rich and cubic Ce-rich phases, produced at low temperatures [31,32], could severely affect the reforming performances of electrodes used in SOFC's devices.…”
Section: Influence Of Humiditymentioning
confidence: 99%